Optimization protocols and improved strategies for metal-organic frameworks for immobilizing enzymes: Current development and future challenges - Cui, Jiandong; Ren, Sizhu; Sun, Baoting; Jia, Shiru (Coordination chemistry reviews, 2018)
[Display omitted] •Enzyme@MOF composites are still at an early stage of development.•Enzyme@MOF composites are a versatile host platform for the effective enzymes immobilization systems.•Different approaches and process optimization of preparing enzyme@MOF composites are evaluated.•There will be great demand on Enzyme@MOF composites with diverse functionality. Metal-organic frameworks (MOFs) are a type of porous material that have tunable porosity, desirable functionality, extremely high surface area, and chemical/thermal stability. MOFs consist of metal containing nodes and organic ligands linked through coordination bonds. Owing to the unique properties of MOFs, there is considerable interest in using them as a potential matrix for enzyme immobilization. Recent studies have focused on developing enzyme-MOF composites with potential applications. Many MOF-enzyme composites exhibit excellent catalytic performance, far outperforming free enzymes in many aspects. This review summarizes recent developments in enzyme-MOF composites with special emphasis on novel synthesizing strategies, process optimization, and improvement of catalytic performance of the enzyme-MOF composites over free enzymes.